Metallothionein Cup1 attenuates nitrosative stress in the yeast Saccharomyces cerevisiae - Yuki Yoshikawa; Ryo Nasuno; Naoki Takaya; Hiroshi Takagi (Microbial Cell, 2022)
Metallothionein (MT), which is a small metal-binding protein with cysteine-rich motifs, functions in the detoxification of heavy metals in a variety of organisms. Even though previous studies suggest that MT is in-volved in the tolerance mechanisms against nitrosative stress induced by toxic levels of nitric oxide (NO) in mammalian cells, the physiological functions of MT in relation to NO have not been fully understood. In this study, we analyzed the functions of MT in nitrosative stress tolerance in the yeast Saccharomyces cerevisiae. Our phenotypic analyses showed that deletion or overexpression of the MT-encoding gene, CUP1, led to higher sensitivity or tolerance to nitrosative stress in S. cerevisiae cells, respectively. We further examined whether the yeast MT Cup1 in the cell-free lysate scavenges NO. These results showed that the cell-free lysate containing a higher level of Cup1 degraded NO more efficiently. On the other hand, the transcription level of CUP1 was not affected by nitrosative stress treatment. Our findings suggest that the yeast MT Cup1 contributes to nitrosative stress tolerance, possibly as a constitutive rather than an inducible defense mechanism.